Skills program for awareness, connectedness, and empowerment: A conceptual framework of a skills group for individuals with a psychosis-risk syndrome - Gupta, Tina; Antezana, Ligia; Porter, Christian; Mayanil, Tushita; Bylsma, Lauren M.; Maslar, Michael; Horton, Leslie E. (Frontiers in Psychiatry, 2023)
Intervention strategies for those diagnosed with psychotic disorders such as schizophrenia can be effective in reducing symptoms and improving quality of life. While strides have been made in developing prevention and intervention strategies earlier on in the disease progression, among those at clinical high-risk (CHR) for psychosis, challenges with heterogeneity can limit symptom and diagnosis specific treatment. Here, we discuss a newly developed therapy skills group called the Skills Program for Awareness, Connectedness, and Empowerment (SPACE) that integrates different types of behavioral skills – standard and radically open dialectical behavioral therapy as well as cognitive behavioral therapy – for CHR youth between the ages of 13-18 years. With the diathesis-stress framework serving as a foundation, the intervention is divided into three stages. These stages target specific signs and symptoms contributing to the progression of CHR symptoms. Stage 1 targets stress (with the goal of developing awareness and reducing distress), stage 2 targets self-disturbances (with a goal of increasing self-connectedness), and stage 3 targets social connectedness (with a goal of improving social domains of functioning). The focus of this article is to introduce the theoretical framework underlying the pilot skills group and discuss ongoing progress.